2014
DOI: 10.1016/j.foodres.2014.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive peptides generated from meat industry by-products

Abstract: 26There is a large generation of meat by-products, not only from slaughtering but also in 27 the meat industry from trimming and deboning during further processing. This results in 28 extraordinary volumes of by-products that are primarily used as feeds with low returns 29 or, more recently, to biodiesel generation. The aim of this work was to review the state 30 of the art to generate bioactive peptides from meat industry by-products giving them an 31 added value. Hydrolysis with commercial proteases constitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
75
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(82 citation statements)
references
References 45 publications
(1 reference statement)
0
75
0
2
Order By: Relevance
“…Similarly, the presence of electron donors (e.g., E, M, N) and amino acids exhibiting chelating activity (e.g., D, E, H, W) also increases the antioxidant activity of the peptides . Comprehensive reviews have been published on the production of antioxidant peptides from proteins of different origin such as: i) aquatic resources (e.g., algae, oysters, mussel, sardine, bonito, tuna, mackerel, yellowfin sole, hok, squid, salmon, eel, round scad, tilapia, channel catfish, horse mackerel, monkfish) (Samaranayaka and Li-Chan, 2011;Wu et al, 2015a, b;Sila and Bougatef, 2016), ii) terrestrial plants (e.g., wheat, corn, rye, kamut, spelt, rapeseed/flaxseed, rice, soybean, cacao seeds, hempseed, pea) (Malaguti et al, 2014;Rizzello et al, 2016), iii) terrestrial animals (e.g., porcine myofibrils, dry-cured ham, buffalo horn, porcine skin) (Mora et al, 2014), iv) dairy (bovine, ovine, buffalo and human milks, whey protein) (Power et al, 2013;El-Salam and El-Shibiny, 2013;Brandelli, et al, 2015), and v) eggs (e.g., egg white ovalbumin, egg white lysozyme, egg yolk) (Yu et al, 2014;Nimalaratne and Wu, 2015). Most studies evaluated the antioxidant activity of the hydrolysates/peptides in vitro using different methods such as DPPH scavenging activity, reducing power, ABTS scavenging activity, Fe 2C chelating activity, b-carotene bleaching preventing activity, linoleic acid autoxidation inhibition activity (Chalamaiah et al, 2012).…”
Section: Antioxidant Propertiesmentioning
confidence: 99%
“…Similarly, the presence of electron donors (e.g., E, M, N) and amino acids exhibiting chelating activity (e.g., D, E, H, W) also increases the antioxidant activity of the peptides . Comprehensive reviews have been published on the production of antioxidant peptides from proteins of different origin such as: i) aquatic resources (e.g., algae, oysters, mussel, sardine, bonito, tuna, mackerel, yellowfin sole, hok, squid, salmon, eel, round scad, tilapia, channel catfish, horse mackerel, monkfish) (Samaranayaka and Li-Chan, 2011;Wu et al, 2015a, b;Sila and Bougatef, 2016), ii) terrestrial plants (e.g., wheat, corn, rye, kamut, spelt, rapeseed/flaxseed, rice, soybean, cacao seeds, hempseed, pea) (Malaguti et al, 2014;Rizzello et al, 2016), iii) terrestrial animals (e.g., porcine myofibrils, dry-cured ham, buffalo horn, porcine skin) (Mora et al, 2014), iv) dairy (bovine, ovine, buffalo and human milks, whey protein) (Power et al, 2013;El-Salam and El-Shibiny, 2013;Brandelli, et al, 2015), and v) eggs (e.g., egg white ovalbumin, egg white lysozyme, egg yolk) (Yu et al, 2014;Nimalaratne and Wu, 2015). Most studies evaluated the antioxidant activity of the hydrolysates/peptides in vitro using different methods such as DPPH scavenging activity, reducing power, ABTS scavenging activity, Fe 2C chelating activity, b-carotene bleaching preventing activity, linoleic acid autoxidation inhibition activity (Chalamaiah et al, 2012).…”
Section: Antioxidant Propertiesmentioning
confidence: 99%
“…This includes bioactive protein hydrolysates and peptides from egg, meat, marine foods, rice and wheat generated using different enzymes such as Alcalase, Papain, Pepsin etc. (Zambrowicz et al 2015;Mora et al 2014;Harnedy and FitzGerald 2012;Cavazos and Gonzalez de Mejia 2013). However, very few studies have been reported on producing protein hydrolysates and peptides by microbial fermentation.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these components are fit for human consumption and contain high amounts of protein, essential amino acids, vitamins, minerals, antioxidants, and bioactive peptides (8, 9). However, for various reasons including regulatory issues, meat industry work practices, and cultural factors (5, 10, 11), a significant volume of such by-products result in low-value products and are often treated as waste with negative environmental and cost implications (12). Finding higher value end-uses for the volume of non-meat components that can arise from meat production will become increasingly important given a projected production increase of 200 million tons of meat by 2050 (13).…”
Section: Introductionmentioning
confidence: 99%
“…(10)], examining sensory aspects of products that contain by-products [e.g., Ref. (15)], and indeed into non-food uses including high value pharmaceutical, cosmetic and nutraceutical use (16), and lower value bioenergy uses (12). …”
Section: Introductionmentioning
confidence: 99%